(untitled) (Plant Tissue Culture and Biotechnology, 2011)
Shoot tip explants of Exacum travancoricum, an endangered herb mainly known for ornamental purpose grown on MS with 4.44 μM BAP and 1.34 μM NAA showed better growth response and produced 29.3 ± 0.3 shoots per explant with an average length of 4.6 ± 0.1 cm after 35 days. Roots were induced after transfer to half strength of MS supplemented with 2.46 μM IBA produced 4.8 ± 0.62 roots with an average height of 3.6 ± 0.10 cm after 30 days. The rooted plantlets were transferred for hardening, 80 per cent of plantlets survived and resumed growth in the mixture of soil, vermiculite and farm yard manure (1 : 1 : 1). Key words: Exacum travancoricum; Shoot tip; Plant regeneration D.O.I. 10.3329/ptcb.v20i2.6889 Plant Tissue Cult. & Biotech. 20(2): 113-118, 2010 (December)